Florida Solid and Hazardous Waste Regulation Handbook: Underground Storage Tanks (UST) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
An underground storage tank is any storage tank that has more than 10 percent of its volume below the surface of the ground. This 10 percent includes piping. USTs are very special and DEP has paid close attention to them, giving them their very own series of regulations. Title 62-761 was passed in 1990 and refers solely to USTs. This regulation also provides that certain types of tanks would be exempt from these regulations. This is EDIS document FE459, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.